What pediatricians can do to further youth violence prevention—a qualitative study. Issue 1 (1st March 1999) - Barkin, Shari; Ryan, Gery; Gelberg, Lillian
Abstract : Objective —Youth violence is a public health problem world wide. However, the United States has the worst rate of youth violence among industralized countries. This study was conducted to learn what pediatricians, community leaders, and parents think the doctor's role is in youth violence prevention during the well-child examination for children. Methods —Interviews were conducted with pediatricians, community leaders, and parents living or working in Los Angeles, California. Results —All three groups interviewed believed that the physician should incorporate violence prevention counseling as part of the well-child examination. The mechanism of action differed for the three groups. Almost half of pediatricians' statements focused on their role as prevention counselor, with respect to such issues as appropriate discipline and gun safety. One third of community leaders' statements, however, related to physician referral to existing community resources. More than half of parents' statements referred to the pediatrician as someone who can directly educate their child about making positive choices. Conclusions —Although pediatricians cannot solve the problem of youth violence alone, findings from this study suggest that they should address this issue with their patients and should work in tandem with existing community resources to further a solution to this growing epidemic.